2015
DOI: 10.1016/j.pbi.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Shoot and root branch growth angle control—the wonderfulness of lateralness

Abstract: The overall shape of plants, the space they occupy above and below ground, is determined principally by the number, length, and angle of their lateral branches. The function of these shoot and root branches is to hold leaves and other organs to the sun, and below ground, to provide anchorage and facilitate the uptake of water and nutrients. While in some respects lateral roots and shoots can be considered mere iterations of the primary root-shoot axis, in others there are fundamental differences in their biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 42 publications
2
67
0
1
Order By: Relevance
“…The growth angle of organs is maintained at specific angles with respect to gravity (gravitropic set-point angle [GSA]) according to developmental control and environmental factors, a concept that provides a unifying explanation for ortho-, plagio-, and diagravitropism (Digby and Firn, 1995). Recent investigations of growth angle control in the lateral roots and shoots of Arabidopsis suggested that an antagonistic interaction between two balancing auxin-dependent growth components, gravitropism and antigravitropic offset, underlies the mechanism of GSA control (Roychoudhry et al, 2013;Roychoudhry and Kepinski, 2015). Based on the concept of GSA control, the growth angle phenotype of lzy1 lzy2 lzy3 lateral roots and shoots might be the result of an imbalance between gravitropism and antigravitropic offset.…”
Section: Discussionmentioning
confidence: 99%
“…The growth angle of organs is maintained at specific angles with respect to gravity (gravitropic set-point angle [GSA]) according to developmental control and environmental factors, a concept that provides a unifying explanation for ortho-, plagio-, and diagravitropism (Digby and Firn, 1995). Recent investigations of growth angle control in the lateral roots and shoots of Arabidopsis suggested that an antagonistic interaction between two balancing auxin-dependent growth components, gravitropism and antigravitropic offset, underlies the mechanism of GSA control (Roychoudhry et al, 2013;Roychoudhry and Kepinski, 2015). Based on the concept of GSA control, the growth angle phenotype of lzy1 lzy2 lzy3 lateral roots and shoots might be the result of an imbalance between gravitropism and antigravitropic offset.…”
Section: Discussionmentioning
confidence: 99%
“…Plant architecture and above ground shape are mainly determined by the number, length, and angle of branches [8]. Appropriate shoot branch angles are required to produce leaves and other organs orientated for the most efficient light interception [41].…”
Section: Discussionmentioning
confidence: 99%
“…Tiller or branch angle has been well investigated among crops including rice and maize, owing to its’ agronomic importance [6,7]. Moreover, the growth angle of branches and other lateral organs are also emerging as important topics for plant developmental research [8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, ~11 genes were reported to control tiller angle in rice [32]. However, in the present study, only TAC1 was detected in the local LD region via GWAS in both Hainan and Wuhan (Table 2).…”
Section: Resultsmentioning
confidence: 57%